Carbohydrate Derivatives and Glycomimetic Compounds in Established and Investigational Therapies of Type 2 Diabetes Mellitus - Somsák, László; Bokor, Éva; Czifrák, Katalin; Juhász, László; Tóth, Marietta (IntechOpen, 2011)
None